2015
DOI: 10.7314/apjcp.2015.16.4.1327
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of MMP9 and MMP2 in Patients with Oral Squamous Cell Carcinoma

Abstract: Background: Squamous cell carcinoma (SCC) is the most common cancer in the oral area. Matrix metalloproteinases (MMPs) and especially MMP-2 and MMP-9 are increased in malignancy and lymph node involvement in oral SCCs. We aimed to evaluate the serum levels of MMP-2 and MMP-9 in patients with oral SCC compared to normal subjects and their relation with clinicopathological findings. Materials and Methods: In this case control study, 20 patients with oral SCC and 20 healthy subjects were included and serum levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…49 Earlier studies by Rosenthal and Matrisian proposed that MMP1, -2, -9, and -14 expression in HNSCC were related to disease progression. 50 Lotfi et al 58 investigated MMP2 and MMP9 serum levels in OSCC patients, and concluded that both were significantly elevated in OSCC patients compared with their healthy counterparts. Significantly, the authors considered MMP2 a better marker for assessing lymph-node metastasis and tumor grade.…”
Section: Mmps As Tumor Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…49 Earlier studies by Rosenthal and Matrisian proposed that MMP1, -2, -9, and -14 expression in HNSCC were related to disease progression. 50 Lotfi et al 58 investigated MMP2 and MMP9 serum levels in OSCC patients, and concluded that both were significantly elevated in OSCC patients compared with their healthy counterparts. Significantly, the authors considered MMP2 a better marker for assessing lymph-node metastasis and tumor grade.…”
Section: Mmps As Tumor Biomarkersmentioning
confidence: 99%
“…Significantly, the authors considered MMP2 a better marker for assessing lymph-node metastasis and tumor grade. 58 A meta-analysis of laryngeal cancers demonstrated that MMP2 expression was higher in cases with lymph-node metastasis, and suggested that upregulation of MMP2 could be instrumental in tumorigenesis, progression, and prognosis in laryngeal cancer. 127 Zhang et al investigated MMP2, -3, and -9 single-nucleotide polymorphisms in esophageal SCC.…”
Section: Mmps As Tumor Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, through observing the serum IL-6 level in patients with tongue cancer, Lotfi A etc. [13] concluded that the serum IL-6 level in patients with tongue cancer was significantly higher than that of the healthy controls. The study of this paper had obtained similar results from the histological level: the expression rate of IL-6 in carcinoma groups was significantly higher than that in the normal tongue tissue and benign tumor, and the expressions among the three groups showed significant difference; the expressions of IL-6 in high differentiation malignant tumor were higher than those in the median differentiation malignant tumor and low differentiation malignant tumor; and all these results indicated that IL-6 played an important role in the genesis and development of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in renal cell carcinoma, oral cavity carcinoma and lymphoma have been reported. In one study increased IL-1α, IL-6, IL-8, vascular endothelial growth factor A (VEGF-a) and TNF-α can predict the development of SCC of the tongue from high-risk neoplasms, and may as potential biomarkers for carcinoma screening (Lotfi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%